2013
DOI: 10.1186/1745-6215-14-381
|View full text |Cite
|
Sign up to set email alerts
|

Decision Aid to Technologically Enhance Shared decision making (DATES): study protocol for a randomized controlled trial

Abstract: BackgroundClinicians face challenges in promoting colorectal cancer screening due to multiple competing demands. A decision aid that clarifies patient preferences and improves decision quality can aid shared decision making and be effective at increasing colorectal cancer screening rates. However, exactly how such an intervention improves shared decision making is unclear. This study, funded by the National Cancer Institute, seeks to provide detailed understanding of how an interactive decision aid that elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Studies have often demonstrated the positive effects of Web-based decision-making tools [25]. Considering this, our research is aimed to more closely identify with and assure patients during the dynamic relationship that is patient-doctor communications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have often demonstrated the positive effects of Web-based decision-making tools [25]. Considering this, our research is aimed to more closely identify with and assure patients during the dynamic relationship that is patient-doctor communications.…”
Section: Discussionmentioning
confidence: 99%
“…Most trials of traditional decision aids demonstrate reduced use of services with marginal benefit and increased use of beneficial services. 23,[49][50][51][52] Although Figure 2 shows decision module users had higher rates of breast and prostate cancer screening, which may not be good for screening services with small or zero net benefit, users self-selected, and module responses indicated a substantial proportion were already inclined to be screened. Randomized controlled trials of similar systems and trials that assess whether decisions better align with values are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the issue of tailoring screening according to the patient’s CRC risk (eg, recommending colonoscopy only to those with increased risk vs offering options to those with average risk) was not discussed. Incorporating patients’ CRC risk in CRC screening discussion is important, and our current website (now renamed as ColoDATES and tested in the field in a federally funded study), includes an interactive risk assessment tool [ 47 ]. Seventh, the focus groups were conducted in 2006 and 2007 and therefore do not necessarily reflect the increased use of EHRs observed over the past few years.…”
Section: Discussionmentioning
confidence: 99%